2019
DOI: 10.1007/s13213-019-01489-0
|View full text |Cite
|
Sign up to set email alerts
|

Potential production of 2-phenylethanol and 2-phenylethylacetate by non-Saccharomyces yeasts from Agave durangensis

Abstract: Introduction The participation of non-Saccharomyces yeasts in fermentation processes is of great importance due to their participation in the formation of esters and superior alcohols, which confer characteristic aromas to beverages such as wine and mescal. The aim The aim of this study was identify and evaluate the potential aroma production of yeast native of Agave fermentation by the mescal production in Durango, Mexico. Isolated yeasts were molecularly identified by 5.8s ribosomal gene; the potential produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Phylogenetic analyses of the obtained sequences were made according to [24] in MEGA-X Program. At first, nucleotide BLAST analysis was done and sequences of reference strains with the sequences of the closest relevant strains (cut-off level: Q cover ≥ 85% and Identity ≥ 90%) were further used in multiple-alignment using MUSCLE program.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Phylogenetic analyses of the obtained sequences were made according to [24] in MEGA-X Program. At first, nucleotide BLAST analysis was done and sequences of reference strains with the sequences of the closest relevant strains (cut-off level: Q cover ≥ 85% and Identity ≥ 90%) were further used in multiple-alignment using MUSCLE program.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Then, there have been efforts for developing biotechnological processes to produce aroma compounds. For example, 2-phenylethanol and 2-phenyl ethyl acetate were produced by Kluyveromyces marxianus (Etschmann et al, 2005;Adler et al, 2011;Adame-Soto et al, 2019). A co-culture Wickerhamomyces anomalus and Saccharomyces cerevisiae (Fan et al, 2019) was used to produce ethyl acetate, while Williopsis saturnus (Yilmaztekin et al, 2009) and Pichia fermentans (Rentería-Martínez et al, 2016;Sanchez-Castañeda et al, 2018) have been used to produced isoamyl acetate.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, Candida glycerinogenes WL2002-5 showed a higher inhibition tolerance to 2-PE than S. cerevisiae W303-1, with no viability reduction in growth at 2 g L −1 of 2-PE (Lu et al, 2016). On the other side, although the growth inhibition of K. marxianus has rarely been assessed, few studies (Adame-Soto et al, 2019) have identified that the production of 2-PE is affected by product inhibition. To this end, several studies (Gao and Daugulis, 2009;Etschmann et al, 2006) have presented strategies to overcome this inhibiting limitation, obtaining promising results regarding the production of 2-PE.…”
mentioning
confidence: 99%